The Influence of the Kampung Santri on The Economic Income of the Ciceri Jaya Community - J Jamaluddin; Nisa Nuranisa; Anisa Fauziah; Yulianis Utami; Hedi Indra Lesmana (Utan Kayu Publishing, 2021)
The international collaboration campaign is a program implemented between two countries, namely Indonesia and Malaysia. The two universities participating in this initiative are Sultan Maulana Hasanuddin Banten State Islamic University (UIN Banten) and Malaysia's Tun Hussein Onn University (UTHM). Several sub-themes will be implemented such as technology, economy, education, cultural history, and covid-19. Economics is one of the sub-themes to be discussed with two types of programs recommended by participants from the two countries in this sub-section, namely disseminating the application of daily financial records, and empowering the entrepreneurship of CiceripikKs. The selection of this program was planned based on the needs of the community / mahasantri in the Kampung Santri